1982
DOI: 10.1093/infdis/146.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Diagnosis of Bone and Joint Tuberculosis by an Enzyme-Linked Immunosorbent Assay

Abstract: Sera from patients receiving treatment for active bone and joint tuberculosis and sera from patients with inactive bone and joint tuberculosis were examined by an enzyme-linked immunosorbent assay for antibody to antigen 6, a homogeneous protein prepared from Mycobacterium tuberculosis strain H37Ra by immunosorbent affinity chromatography. Sera from 21 control subjects had a geometric mean titer of 1:6 with no difference between tuberculin purified protein derivative-positive and -negative patients. Sera from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…Recent studies have shown encouraging results with enzyme-linked immunosorbent assays (ELISA) for the serodiagnosis of tuberculosis (Nassau, Parsons and Johnson, 1976;Tandon et al, 1980;Stroebel et al, 1982;Benjamin and Daniel, 1982;Kalish et al, 1983;. There have been some differences in the ELISA methodology, but the major differences have been in the antigens used to detect antibody in patient and control sera.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown encouraging results with enzyme-linked immunosorbent assays (ELISA) for the serodiagnosis of tuberculosis (Nassau, Parsons and Johnson, 1976;Tandon et al, 1980;Stroebel et al, 1982;Benjamin and Daniel, 1982;Kalish et al, 1983;. There have been some differences in the ELISA methodology, but the major differences have been in the antigens used to detect antibody in patient and control sera.…”
Section: Introductionmentioning
confidence: 99%
“…This antigen reacts with sera from most patients having multibacillary or advanced pulmonary tuberculosis, but it is poorly recognized in sera from patients having low bacillary counts in sputum and from asymptomatic infected persons (for examples, see references 7, 9, 15, 32, and 43). Likewise, antibodies against the Ag85 complex are associated with smear-positive pulmonary disease and correlate with the extent of disease as determined by radiography, while they are absent in patients with past tuberculosis infections, asymptomatic infections, or recent exposures to M. tuberculosis (5,11,34,35). The high-level transcription of esat-6 in both multiplying and nonreplicating tubercle bacilli also fits well with the notion that ESAT-6 induces cellular immune responses in both active disease and in latent infection (3,13,27,39).…”
mentioning
confidence: 99%
“…It is possible that our results could have been affected by the inclusion of a large number of patients with extrapulmonary and smear-nega tive disease. Although the reliability of the ELISA test has not been widely assessed in patients with extrapulmonary tuberculosis, Stroebel et al [22] and Chawla et al [23] have reported encouraging results.…”
Section: Discussionmentioning
confidence: 99%